2020
DOI: 10.1016/j.psj.2020.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with vitamin C ameliorates the adverse effects of Salmonella Enteritidis-challenge in broilers by shaping intestinal microbiota

Abstract: Salmonella Enteritidis ( SE ) infection is not only a leading cause of poor production performance and compromised animal welfare in broilers but also a potential threat to public health. Two experiments were conducted to evaluate the effects of dietary supplemental vitamin C ( VC ) on SE challenged-broilers. In experiment 1, one hundred eighty 1-day-old Arbor Acre broilers were randomly allocated into 3 treatments, with 0, 500, or 1,000 mg/kg VC include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…There are no reports so far on the effect of supplemental VK on performance of laying hens challenged with SE, but similar to our findings in non-challenged birds [18] did not observe any effect of 10 mg/kg VK addition to the diet of LSL White Leghorn laying hens on birds' egg production. If birds were challenged with SE, however, a higher mortality rate was obtained in the present study which is in agreement with observations in Arbor Acre broilers [5].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are no reports so far on the effect of supplemental VK on performance of laying hens challenged with SE, but similar to our findings in non-challenged birds [18] did not observe any effect of 10 mg/kg VK addition to the diet of LSL White Leghorn laying hens on birds' egg production. If birds were challenged with SE, however, a higher mortality rate was obtained in the present study which is in agreement with observations in Arbor Acre broilers [5].…”
Section: Discussionsupporting
confidence: 93%
“…Salmonella enterica serovar Enteritidis ( Salmonella Enteritidis), a Gram-negative bacterium, is the prevalent egg-product-related foodborne pathogen [ 3 ]. Infections with Salmonella Enteritidis (SE) are known to affect the health conditions of chickens [ 4 , 5 ] resulting in the loss of homeostasis which, in turn, will reduce chickens’ production performance.…”
Section: Introductionmentioning
confidence: 99%
“…The inoculation of Eimeria spp decreased the expression of PepT1 in the jejunum of broilers (Khatlab et al, 2019). Gan et al (2020) reported decreased villus height in the jejunum after Salmonella Enteritidis challenge. Fasina et al (2010) reported decreased villus surface area in the jejunum of broiler chicks infected with Salmonella Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C can alleviate the effects of multiple stressors in animals and, alone or with other compounds such as curcumin, allows a reduction in Salmonella spp. count [ 89 , 90 , 91 ] and an improvement of the intestinal health [ 92 ]. Feed supplementation with vitamin E results in reduction in oxidative and immune stress that occurs during the infection [ 93 ] and its combination with arginine increases resistance against bacterial colonization, although there is no reduction in the concentration of S. Typhimurium in ceca [ 94 ].…”
Section: Salmonella Spp Infectionmentioning
confidence: 99%